A Pastoral Care Model for Enhancing Students’ Well-Being at Secondary Schools Under the Saint Gabriel’s Foundation, Thailand - Yuchompoo, Sarawut; Mhunpiew, Nathara; Kaewprasit, Siam (ABAC ODI JOURNAL Vision. Action. Outcome, 2025)
Pastoral Care in secondary education is essential for promoting students' well-being by addressing their physical, emotional, social, and spiritual needs. This study aimed to develop a Pastoral Care Model to enhance students' well-being in secondary schools under the Saint Gabriel's Foundation in Thailand. Employing a mixed-method research approach, the study identified nine key components of student well-being: physical and mental health, emotional health, social health, spiritual health, positive emotions, engagement, relationships, meaning, and accomplishment. Data were collected from 1,322 students, resulting in a response rate of 97.92%. The study revealed the top four priority needs for pastoral care as physical and mental health (PNImodified = 0.1009), emotional health (PNImodified = 0.0973), positive emotion (PNImodified = 0.0806), and meaningfulness (PNImodified = 0.0737). The proposed Pastoral Care Model was developed based on the PERMA framework, spiritual leadership principles, and validated by qualitative expert, leading to the formulation of five implementation frameworks: WISE Mind, CARE Plus, PURPOSE Pathways, BRIDGE Model, and SHINE System. The findings contribute to a culturally responsive and evidence-based pastoral care approach, integrating Catholic educational values with contemporary well-being strategies. This research underscores the importance of a structured, holistic pastoral care model in fostering student resilience, engagement, and overall well-being, ensuring that schools serve as supportive environments for students' personal and academic development.